2020
DOI: 10.3390/ijerph17176209
|View full text |Cite
|
Sign up to set email alerts
|

Topic Modeling for Analyzing Patients’ Perceptions and Concerns of Hearing Loss on Social Q&A Sites: Incorporating Patients’ Perspective

Abstract: Hearing loss is the most common human sensory deficit, affecting normal communication. Recently, patients with hearing loss or at risk of hearing loss are increasingly turning to the online health community for health information and support. Information on health-related topics exchanged on the Internet is a useful resource to examine patients’ informational needs. The ability to understand the patients’ perspectives on hearing loss is critical for health professionals to develop a patient-centered interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
0
15
0
2
Order By: Relevance
“…20 However, the use of topic modelling techniques in Ear, Nose and Throat-related research is sparse, and there is limited manual evaluation of the accuracy of automatically-generated topics. 21,22…”
Section: Introductionmentioning
confidence: 99%
“…20 However, the use of topic modelling techniques in Ear, Nose and Throat-related research is sparse, and there is limited manual evaluation of the accuracy of automatically-generated topics. 21,22…”
Section: Introductionmentioning
confidence: 99%
“…Medical and dental clinicians can utilize ML algorithms to manage and analyze the immense data present in patients' health records to extract meaningful information that can be used to improve population health and wellbeing (12). Diagnostic medicine incorporates advanced AI technologies to predict or diagnose disease and assist in the clinical decision-making process (9)(10)(11), and several studies have shown that AI-based comprehensive care system has great potential to enhance patient care, spur innovative research, and facilitate information sharing (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…To date, not many studies have performed auditory training for improving spatial hearing abilities. A comprehensive understanding of hearing loss is crucial for designing an intervention program (Bahng & Lee, 2020). Firszt et al (2015) developed the localizationspecific auditory training for unilateral severe to profound hearing loss and reported that eight out of 11 participants' spatial hearing abilities improved significantly.…”
Section: Introductionmentioning
confidence: 99%